2020
DOI: 10.1136/bmjopen-2019-032921
|View full text |Cite
|
Sign up to set email alerts
|

Knowing what the patient wants: a hospital ethnography studying physician culture in shared decision making in the Netherlands

Abstract: ObjectivesTo study physician culture in relation to shared decision making (SDM) practice.DesignExecution of a hospital ethnography, combined with interviews and a study of clinical guidelines. Ten-week observations by an insider (physician) and an outsider (student medical anthropology) observer. The use of French sociologist Bourdieu’s ’Theory of Practice’ and its description of habitus, field and capital, as a lens for analysing physician culture.SettingThe gynaecological oncology department of a university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Social science shows medicine had always had a more ‘human’ aspect to it than science would claim. Practical knowledge, intuition and nuances in the physician–patient relationship have always been very important not just to how decisions around health and illness have been made, but also to what constitutes the professions in health care (Kim et al, 2018; Spinnewijn et al, 2020). Second, if decisions are taken based on historical data, existing categories might be reified and naturalised (Mau, 2017; Mennicken and Espeland, 2019; Quinn, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social science shows medicine had always had a more ‘human’ aspect to it than science would claim. Practical knowledge, intuition and nuances in the physician–patient relationship have always been very important not just to how decisions around health and illness have been made, but also to what constitutes the professions in health care (Kim et al, 2018; Spinnewijn et al, 2020). Second, if decisions are taken based on historical data, existing categories might be reified and naturalised (Mau, 2017; Mennicken and Espeland, 2019; Quinn, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, decisions in the field of medicine seem to be far more complex, entail much more information and rely on manifold practices as studies, e.g. in medical anthropology, show (Kim et al, 2018; Spinnewijn et al, 2020).…”
Section: Different Sorts Of Data – Different Consequences?mentioning
confidence: 99%
“…Robust MDT decisions provide an important basis for shared decision-making, which implies a shift in focus from the healthcare provider to the patient. Access to complete information, consideration of patient needs, recognition of barriers for implementation, and balancing risk and benefits support provision of treatment recommendations that are found appropriate and acceptable by the patient [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians may act on what they think is best for patients, rather than explore what patients actually want. 54 Further, clinicians’ attitudes toward shared decision making tend to be largely positive but also coupled with reluctance to share decisional control and a lack of understanding of the concept. 55 , 56 Forcino et al, 55 for example, found that among 272 US-based clinicians involved in family medicine or surgery, up to half reported feeling uncomfortable with decisions that stray away from what they think is clinically most appropriate.…”
Section: Discussionmentioning
confidence: 99%